Uncertainty Analysis and Resource Allocation in Construction Project Management. Issue 4 (2nd October 2018) - Zhong, Yong; Chen, Zhigao; Zhou, Zhong; Hu, Haibo
Abstract: The premise of dealing with uncertainty in this article is to figure out the impact of uncertainties on project performance. This article proposes a framework for quantitative analysis that combines a fuzzy mathematics approach with system dynamics theory. Simulations generated using a model based on the framework show that uncertainties affect project performance by changing project parameters, and the mechanisms involved depend on the sources of the uncertainties. Furthermore, while technical and financial uncertainties mainly influence project costs, uncertainties related to markets, regulations, and organizational structures affect both project duration and cost. Finally, strategies for coping with uncertainties in a resource allocation perspective are presented.